Muerte cruzada en el sistema de pesos y contrapesos: relación entre ejecutivo y legislativo bajo la mirada de la Constitución del 2008 - Cabezas Quilumbaquin, Karla Lizbeth (2024)
The present research work aims to describe the cross-death within the system of weights and counterweights, contemplated in the Constitution of Ecuador of 2008, through the analysis of the constitutional norm seeking to identify the characteristics and requirements of this figure with the purpose of resolving doubts arising after the dissolution process that Ecuador experienced in May 2023. It can be specified that the system of weights and counterweights is one of the fundamental characteristics of the dissolution or division of powers and the importance of complying with the constitutional regulations was highlighted, by mentioning the different grounds for its correct application. It can be evidenced that within the present study the system of weights and counterweights is highlighted as an effective tool that helps the cross death to prevent bad abusive and authoritarian decision making, being very important to mention that the cross death does not affect the stability of the system of weights and counterweights is more its use as a whole highlight the complementarity between these two. In summary, the study emphasizes the positive synergy between cross-death and the system of checks and balances in the political and legal context of Ecuador. The research has a qualitative approach of a descriptive nature. It will employ both theoretical and practical methods, which can be found in literary works and academic texts, and will be complemented with interviews to experts in the field.